Advances About Immunoinflammatory Pathogenesis and Treatment in Diabetic Peripheral Neuropathy - Xue, Tianyu; Zhang, Xin; Xing, Yiwen; Liu, Shuhan; Zhang, Lijun; Wang, Xun; Yu, Min (Frontiers in Pharmacology, 2021)
Most diabetic patients develop diabetic peripheral neuropathy (DPN). DPN is related to the increase of inflammatory cells in peripheral nerves, abnormal cytokine expression, oxidative stress, ischemia ,and pro-inflammatory changes in bone marrow. We summarized the progress of immune-inflammatory mechanism and treatment of DPN in recent years. Immune inflammatory mechanisms include TNF-α, HSPs, PARP, other inflammatory factors, and the effect of immune cells on DPN. Treatment includes tricyclic antidepressants and other drug therapy, immune and molecular therapy, and non-drug therapy such as exercise therapy, electrotherapy, acupuncture, and moxibustion. The pathogenesis of DPN is complex. In addition to strictly controlling blood glucose, its treatment should also start from other ways, explore more effective and specific treatment schemes for various causes of DPN, and find new targets for treatment will be the direction of developing DPN therapeutic drugs in the future.